2019
DOI: 10.1016/j.jad.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal decreases in suicidal ideation are associated with increases in salience network coherence in depressed adolescents

Abstract: Background: Suicidal ideation (SI) is an important predictor of suicide attempt, yet SI is difficult to predict. Given that SI begins in adolescence when brain networks are maturing, it is important to understand associations between network functioning and changes in severity of SI. Methods: Thirty-three depressed adolescents were administered the Columbia-Suicide Severity Rating Scale to assess SI and completed resting-state fMRI at baseline (T1) and 6 months later (T2). We computed coherence in the executiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…In terms of neuroimaging correlates, at uncorrected level, we found several regions associated with suicidality not consistently reported in the literature 18 ; and those regions that we found that have been reported (e.g. aberrant thickness in medial orbitofrontal gyrus, aberrant connectivity in the default mode and salience networks, or aberrant task-elicited activations in temporal lobe and insula) differed in directionality or specific regions involved 18,38,39,[54][55][56][57] . Moreover, after FDRcorrection, we only found a thinner left bank of the superior temporal sulcus in the caregiverreported suicidality analysis.…”
Section: Discussionmentioning
confidence: 65%
“…In terms of neuroimaging correlates, at uncorrected level, we found several regions associated with suicidality not consistently reported in the literature 18 ; and those regions that we found that have been reported (e.g. aberrant thickness in medial orbitofrontal gyrus, aberrant connectivity in the default mode and salience networks, or aberrant task-elicited activations in temporal lobe and insula) differed in directionality or specific regions involved 18,38,39,[54][55][56][57] . Moreover, after FDRcorrection, we only found a thinner left bank of the superior temporal sulcus in the caregiverreported suicidality analysis.…”
Section: Discussionmentioning
confidence: 65%
“…In depressed adolescents, greater severity of SI has been associated with both greater connectivity between one node of the DMN (precuneus) with sensorimotor regions, as well as lower connectivity between another node of the DMN (PCC) with visual attention regions (23). In another sample of depressed adolescents, researchers documented lower network coherence (i.e., within-network connectivity) of the anterior node of the DMN (medial PFC), SN (centered on the dACC) and left CEN (24) in relation to participants' most severe intensity of SI in the lifetime; further, longitudinal increases in network coherence of the SN (centered on the dACC) in this same sample were also associated with decreases in severity of SI (25). Compared to healthy controls, transdiagnostic samples of young adults (who were primarily diagnosed with depression) with history of SI were found to exhibit lower connectivity between the SN (dACC) and DMN (specifically, dorsal PCC relative to ventral PCC; 26).…”
Section: Introductionmentioning
confidence: 71%
“…Contrary to our hypotheses, which were guided by previously published literature, we did not find group differences with respect to SI history in network coherence or between-network connectivity of the CEN or SN-ACC. Previous work from our group using similar analytical approaches (i.e., group ICA combined with dual regression) in an independent sample of depressed adolescents (24,25) found that lower CEN, DMN-A, and SN-ACC coherence levels were associated with greater intensity of the most severe experience of SI in the lifetime (24), and that longitudinal changes in SN-ACC coherence were associated with changes in SI severity (25). Another study also reported that compared to healthy controls, young adults (who were primarily diagnosed with depression) with SI had lower dorsal ACC low frequency BOLD activity and relative connectivity (with dorsal versus ventral PCC; Chase et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For adolescents, cognitive flexibility, or the ability to alter thinking and shift attention away from incorrect responses following negative feedback, has been shown to prospectively predict suicidality (Miranda et al, ). Additionally, cognitive abilities have demonstrated the ability to differentially predict young‐adult depressive symptoms, SI, and suicide attempts in a longitudinal studies with adolescents (Crandall, Allsop, & Hanson, ; Schwartz, Ordaz, Ho, & Gotlib, ). Taken together, the literature on neuropsychological correlates of SI for adolescents and adults suggests a need to investigate how these neuropsychological deficits interact with other known risk factors to impact suicidality in adolescence prior to the initial emergence of ideation.…”
mentioning
confidence: 99%